How is occupational identity affected by the family environment of publicly funded students in local normal colleges? A moderated mediation model - Zhang, Jia; Liu, Yang; Mao, Zhi; Xiao, Bei (Frontiers in Psychology, 2023)
The occupational identity of local publicly funded students is associated with the stability of rural teachers. To discuss the influence mechanism of family environment, psychological capital, and professional commitment on occupational identity, this study examined 395 local publicly funded students with the occupational identity scale, psychological capital scale, professional commitment scale compiled, and family environment scale in china. We found no significant difference in terms of gender, source of birth, only children or not, and from teachers' families or not. Junior students' occupational identity was significantly higher than freshmen. In addition, we found that psychological capital plays a total meditation role between family environment and occupational identity. Psychological capital explains the influence of family environment on occupational identity. While the moderating role of professional commitment on the family environment and psychological capital is not supported in this study, it positively moderates the meditation role of psychological capital and occupational identity. Overall, this study will be significant in improving the training quality of local publicly funded students.